2022
DOI: 10.1182/bloodadvances.2021006889
|View full text |Cite
|
Sign up to set email alerts
|

A prognostic model to predict survival after 6 months of ruxolitinib in patients with myelofibrosis

Abstract: Ruxolitinib (RUX) is extensively used in myelofibrosis (MF). Despite its early efficacy, most patients lose response over time and, after discontinuation, have a worse overall survival (OS). Currently, response criteria able to predict OS in RUX-treated patients are lacking, leading to uncertainty regarding the switch to second-line treatments. In this study, we investigated predictors of survival collected after six months of RUX in 209 MF patients participating in the real-world ambispective observational RU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 57 publications
4
42
0
Order By: Relevance
“…As of note, OS was not different between RUX-treated patients who were TI and not TI at week 24 in long-term pooled analyses from the COMFORT-I and COMFORT-II phase 3 trials [ 13 ]. However, transfusion need at several timepoints following treatment with RUX was associated with shortened survival in a real-world observational study in MF, and was subsequently incorporated into the Response to Ruxolitinib After 6 Months (RR6) prognostic model that may help to predict which patients will benefit from a prompt treatment switch from RUX [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As of note, OS was not different between RUX-treated patients who were TI and not TI at week 24 in long-term pooled analyses from the COMFORT-I and COMFORT-II phase 3 trials [ 13 ]. However, transfusion need at several timepoints following treatment with RUX was associated with shortened survival in a real-world observational study in MF, and was subsequently incorporated into the Response to Ruxolitinib After 6 Months (RR6) prognostic model that may help to predict which patients will benefit from a prompt treatment switch from RUX [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…OS was not significantly different between RUX-treated patients who were transfusion independent and not transfusion independent at week 24 [ 13 ], whereas a significant prognostic improvement was demonstrated in RUX-treated patients who experienced spleen volume reduction at week 24 compared to those who did not [ 14 ]. In an observational study of RUX-treated patients with MF, red blood cell transfusion need at baseline, 3 months, and 6 months of treatment was negatively correlated with OS [ 15 ]. Further, a real-world study of intermediate- to high-risk MF patients demonstrated that OS was significantly improved in the five years following RUX approval compared with the two years prior; notably, in the RUX post-approval time frame, OS was greater for those who received RUX versus those who did not [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other contemporary investigations have examined multiparameter flow cytometry as a substitute for blast count and response to ruxolitinib treatment after 6 months as potential predictors of survival. 10,11 Improved survival seen with ruxolitinib use has been further validated on other real-world datasets, with the mechanism of improvement likely multifactorial including less debilitation, slower rates of leukaemic transformation, and fewer disease-associated complications. 12 Higher baseline QOL might also be associated with less diseaserelated debilitation, decreased hospitalisations, and fewer life-threatening complications.…”
Section: Quality Of Life Independently Predicts Overall Survival In M...mentioning
confidence: 93%
“…Most of the physicians in this study considered treatment failure as the lack of SVR35% at 6 months, a suboptimal response as the lack of a minimal clinical benefit within 6 months, and progression as a >25% increase in SV from baseline or nadir or an increased WBC count together with decreased platelet counts and worsening of anemia. More recently, a prognostic model has been proposed to predict survival after 6 months of ruxolitinib in patients with MF [ 16 ].…”
Section: Discussionmentioning
confidence: 99%